2017
DOI: 10.1111/jfpp.13237
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional, microbial and physicochemical changes in pear juice under ultrasound and commercial pasteurization during storage

Abstract: In this study, the microbial and nutritional aspects of pear juice with conventional or ultrasound (US) treatment during storage at 4  °C were studied. The conventional pasteurization was 95 °C for 5 min while US‐pasteurizations (frequency 30 kHz, amplitude 70%) were 25, 45, and 65 °C for 10 min, under a probe sonicator (750 W). Control, US25 and US45 had shelf lives of 9, 12, and 15 days respectively. Ascorbic acid, total phenols, total anti oxidant capacity, and cloud value decreased in all treatments while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
(67 reference statements)
3
12
0
1
Order By: Relevance
“…Data for the influence of storage time on the stability of TP in the samples showed significant reduction in stability of phenolic compounds with increased storage (7 days vs. 0 day). Obtained results are accordant with another research, where sonicated (750 W, 30 kHz, A = 70%, 25, 45, and 65°C, 10 min) pear juice samples had notable decrease in TP during 21 days of long storage at 4°C (Saeeduddin et al, ). Additional to findings for orange and sweet lime juices that were treated with ultrasound (Khandpur & Gogate, ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Data for the influence of storage time on the stability of TP in the samples showed significant reduction in stability of phenolic compounds with increased storage (7 days vs. 0 day). Obtained results are accordant with another research, where sonicated (750 W, 30 kHz, A = 70%, 25, 45, and 65°C, 10 min) pear juice samples had notable decrease in TP during 21 days of long storage at 4°C (Saeeduddin et al, ). Additional to findings for orange and sweet lime juices that were treated with ultrasound (Khandpur & Gogate, ).…”
Section: Resultssupporting
confidence: 90%
“…Obtained values are in accordance with research who reported influences of ultrasound (650 W, 20 kHz, D = 6 mm, 30 min, 20°C) and storage (8 days, 15, 15, and 25°C) on black mulberry juice samples with significant reduction in antioxidant capacity (Jiang et al, ). Another study demonstrated that sonicated pear juice samples (750 W, 30 kHz, A = 70%, 25, 45, and 65°C, 10 min) had notable decrease in TP and total antioxidant capacity during 21 days of storage at 4°C (Saeeduddin et al, ). The possible reason for the reduced antioxidant capacity observed could be explained with strong polyphenolic tendency toward polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…However, Johansson et al (2016) showed that ultrasound treatment does not significantly influence the oxidative changes in milk and they concluded that the lipid oxidation derived volatiles produced are below the human sensory detection level. The study of Saeeduddin et al (2017) indicated that ultrasound-pasteurization is a promising pear juice processing technology at low temperature, retaining bioactive compounds, meeting safety standards, and increasing shelf life.…”
Section: Psychrophilic Bacteriamentioning
confidence: 99%
“…Agriculturally accessible 'on-site' juice processing technologies are extensive, ranging from; blender-style processing [33][34][35][36][37][38], commercial and cold-press juicing [35,39,40], as well as various forms of manual pressing [41]. The effect of juicing technologies on nutritional content, is studied [35] with regard to; apple, pear, persimmon and mandarin fruits, where the effect of processing methods on phytochemical content and was demonstrated to be statistically significant (p < 0.05) between juice-style and blender-style techniques.…”
Section: Introductionmentioning
confidence: 99%